Presenting clinical features of COVID-19 in neonatal age group - Rahman, Maksudur; Jahan, Nishat; Hoque, Md Mahbubul; Ghosh, Kinkar (Northern International Medical College Journal, 2023)
Background : In December, 2019 a cluster of pneumonia cases spread in Wuhan City, Hubei Province, China caused by a novel corona virus (named as “2019-nCoV”). Although it is thought to be a disease of adult but it can occur in children and neonates also. Objective : The aim of this study was to see the incidence of Neonatal COVID-19 and its mode of presentation in neonatal age group. Methods : This cross sectional study was done in Dhaka Shishu (Children) Hospital from April, 2020 to October, 2020. All suspected neonates for COVID-19, RT PCR were done from nasopharyngeal swab. Suspecting sign were fever, respiratory difficulty, reluctant to feed, neonate not responding to conventional treatment, or referred from endemic area or having any household contact. Routinely RT PCR was done preoperatively who needed surgery. Then all the data were collected and analyzed using Statistical Package of Social Science (SPSS), version 26. Results : Total 5521 neonates were admitted and 299 neonates were suspected for COVID-19 infection during this study periods and undergone RT PCR, out of which 47 cases were test positive. The incidence of COVID-19 cases was 0.85% among hospitalized neonates. Thirty one were male and 16 were female. Male female ratio was 1.9:1. Thirtythree cases admitted in medicine and 14 cases in surgery division. Twenty three (49%) cases presented symptoms after 7 days of age and 13(28%) cases got admitted within 3 days, among them 2 cases were admitted at 24 hours of age with symptoms. Respiratory difficulty (25.5%), convulsion (19.1%), fever (17%) and reluctant to feed (17%) were common presenting symptoms. The associated diagnosis with COVI-19 cases were mostly perinatal asphyxia, septicemia and pneumonia. Regarding chest X-ray, one neonate had patchy opacities in right lower lobe, another had bilateral ground-glass opacity and in case of third one few patchy opacities was found in the right perihilar region. Out of 47 positive cases 23 patients could discharge after improvement, 14 patients referred to COVID specialized hospital, 2 cases went as LAMA (Leave against medical advice) and 8 patients died at our hospital. Conclusion : In this Study the incidence of COVID-19 in newborn was 0.85% among hospitalized newborn. The common clinical features were respiratory difficulty, convulsion, fever and reluctant to feed. It could not be differentiated whether these clinical features were due to COVID-19 or associated diseases. Northern International Medical College Journal Vol. 12 No.2 Jan 2021, Page 526-529